Platelet activation by platelet aggregation factor from Eisenia foelide - Qing Rong; Zhou Yuan-gong; Zhuang Qin-qi (Acta Pharmacologica Sinica, 2016)
A platelet activating factor from earthworm, Eisenia foelide (EPAF, 25.9 mumol.L-1), induced human platelet aggregation and 5-HT (maximal release of 89% at EPAF 74.1 mumol.L-1) was detected during this process. Neither creatine phosphate/creatine phosphate kinase (CP/CPK) nor aspirin completely inhibited the EPAF-induced platelet aggregation. In the presence of fibrinogen, EPAF (55.6 mumol.L-1) induced the aggregation of human platelet which had been thrombin-treated and degranulated. Results indicated that EPAF was a potent platelet agonist and the EPAF-induced platelet aggregation was ADP- and TXA2-independent.